Ketentuan Kesucian Dalam Hubungan Suami-Istri-Analisis Tafsir Ibnu Katsir Terhadap Surah Al-Baqarah Ayat 222 - Farah Achmanda Kesuma Dianti; Shoffa Arfanul Adha (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
The requirement of chastity in a married relationship becomes an important point in the doctrine of Islam that is explained in the qur 'an. Among the scriptures that discuss this issue is surah al-baqarah verse 222. This text was intended to analyze ibn katsir's interpretation of the text. In its interpretation, ibn katsir describes the laws and conditions that pertain to chastity in married relationships, including sacred and unholy times for women, and how to cope with them in the context of daily life. An analysis of ibn katsir's interpretation gives insight into the traditional understanding of chastity in Islam, and provides a relevant view of coping with it in today's life. Keywords : chastity clause, tafsir ibn katsir, surah al-baqarah verse 222